THE RELATIONSHIP OF ONLINE GAME ADDICTION WITH SLEEP QUALITY IN YOUTH IN RT 002 KP. CENTRAL KALIABANG KARENGAN - Lestari, Sri Mubdi Lestari; Simamora, Rotua Suriany; Meliyana, Ernauli (Soscience: Jurnal Ilmu Sosial Science, 2023)
The rapid development of science and technology in this era brings many changes from all walks of life, the most prominent development in this era is the internet. At this time the internet is not only used to meet information needs, but also for things that are entertainment, one of the entertainment on the internet is online games. Online games are electronic and visual games that can be played by many players at once using the internet. Playing online games excessively can lead to lack of sleep, disturbed sleep patterns, poor sleep quality and lead to mental health problems. Playing too much online games can make a teenager addicted.The purpose of this study was to determine the relationship between addiction to playing online games with adolescent sleep quality in RT 002 Kp.Pengarengan Central Kaliabang. The research method used is quantitative with cross-sectional analytic research. The population in this study of late teens amounted to 60 respondents. Data collection technique using simple random. The results showed that the chi square test results p-value (0.000) < (0.05) there was a relationship between Online Game Addiction and Sleep Quality in Teenagers in RT 002 Kp.Pengarengan Central Kaliabang.